Utilization of Reduced Haploid Vigor for Phenomic Discrimination of Haploid and Diploid Maize Seedlings. Issue 1 (1st March 2019) - Vanous, Kimberly; Jubery, Talukder Zaki; Frei, Ursula K.; Ganapathysubramanian, Baskar; Lübberstedt, Thomas
Abstract : Core Ideas: There are many potential benefits of incorporating embryo culture into a doubled haploid program. There is no known non‐transgenic method of selecting haploid embryos following embryo culture. Our goal was to establish a non‐transgenic haploid selection method following embryo culture. These methods allow early haploid selection based on differential root growth features. Potential benefits of incorporating embryo culture (EC) into a doubled haploid (DH) program, including shortening the breeding cycle and increasing chromosome doubling rates, make the laborious and tedious task of excising embryos worth the effort. Difficulties arise during embryo selection considering the marker gene R1‐nj, which is typically used in DH programs, is not expressed in early stages after pollination. Although transgenic approaches have been implemented to bypass this issue, there is so far no known non‐transgenic method of selecting haploid embryos. The findings of this study reveal methods of selecting haploid embryos that allow the possibility of incorporating EC into a DH program without using transgenic inducers. The best performing method involves a machine‐learning classifier, specifically a support vector machine, which uses primary root lengths and daily growth rates as traits for classification. Selection by this method can be achieved on the third day after germination. By this method, an average false negative rate of 2% and false positive rate of 9% was achieved. Therefore, the methods presented in this research allow efficient and non‐transgenic selection of haploid embryos that is simple and effective.